THE PERSPECTIVES OF CELLULAR THERAPY IN REHABILITATION TREATMENT OF NEUROLOGICAL PATIENTS (REVIEW OF LITERATURE WITH OWN RESEARCH DATA) - V. Lychko (Eastern Ukrainian Medical Journal, 2019)
The article gathers and analyses modern data from foreign and regional authors regarding the latest achievements in cellular technologies that have prospects in rehabilitation of neurological patients. For the replacement of damaged brain tissue, technologies directed for differentiation of stem cells in neuronal and glial directions are extremely promising. Today, it is feasible to expect that in the near future this will enable the transplantation of cells to activate the processes of neuroplasticity in recovery period.The data of own researches, which examined changes in structural and functional characteristics of brain tissue of rats with condition of experimental acute focal cerebral ischemia (AFCI) in dynamics of treatment cryopreserved cord blood serum (CCBS) was given for evaluation of its membrane protection, immune modulation and proangiogenic activity.The study was conducted on 60 outbred white male Wistar rats weighing 200±20 g. All animals were divided into 3 groups: 1st group (controls) – intact rats without trauma and treatment; 2nd group – animals after modelling AFCI without treatment; 3rd group – rats after modelling AFCI, which was administered CCBS.The results of the study indicated the stimulating effect of the components of CCBS on restoration of ultrastructure of the damaged capillaries, increasing their density, as well as the formation of new capillaries. It was found that the average area of the perivascular spaces, which is an indicator of vasogenic edema in rats of group 2 is 45 times higher than that in group 1, while in rats in group 3 treated with CCBS, this figure was exceeded 37 times. The average area of pericellular spaces, indicating the degree of cytotoxic edema, in rats of group 2 on the 7th day after AFCI is almost 23 times higher than the results of group 1. This indicator in rats of group 3 was increased by 20 times compared with group 2. On the 7th day of the experiment in rats of group 2, the surface area of endothelial cells was significantly larger than in rats of groups 1 and 3 by 54.1% and 31.6% respectively.Neurotrophic therapy is a very promising area of regenerative medicine, which requires further study in the use of growth factors.